Effects of Bi2Se3 Amount in Thermoelectric Performance of Bi2(TeSe)3 Materials Fabricated by High‐Energy Ball Milling. Issue 4 (8th April 2016) - Rimal, Pradip; Han, Seung Tek; Hong, Soon‐Jik; Kim, Hyo‐Seob; Cho, Kuk Young; Lee, Ilsueuk
Abstract : Amount of Bi2 Se3 has significant role in controlling thermoelectric properties of n‐type Bi2 (TeSe)3 material. In this study, effects of Se alloying amount in Bi2 (TeSe)3 thermoelectric materials fabricated by high‐energy ball milling and spark plasma sintering were studied and compared with other fabrication methods. Amount of Bi2 Se3 (5%, 10%, 15%, and 20%) did not have any significant effect over fabricated powder size, grains of consolidated bulks, and mechanical properties; however, electrical properties and thermoelectric efficiency were noticeably influenced. Both carrier concentration and carrier mobility decreased with increase in Se amount. In total, 20% Se alloying was effective in improving thermoelectric figure of merit ZT value by almost 40% compared with only 5% Se alloying.